Corruption, Bureaucracy and Firm Productivity in Africa. Issue 1 (22nd January 2013) - Faruq, Hasan; Webb, Michael; Yi, David
Abstract This paper estimates the impact of corruption and poor bureaucratic quality on firm productivity for a unique dataset with firm‐specific data of more than 900 firms over 12 years for Ghana, Kenya and Tanzania. We first discuss why poor bureaucratic quality and, especially, corruption are expected to have negative impacts on firm productivity. We then employ Data Envelopment Analysis to estimate firm productivity and pooled OLS and Tobit regression analysis to estimate the effects of corruption and bureaucratic quality on firm productivity. We find that less productive firms are more likely to engage in corrupt activities; both poor bureaucratic quality and corruption reduce firm productivity; and corruption has a greater negative impact on productivity.